Challenges of organic amendments: Impact of vermicompost leachate and biochar on popcorn maize in saline soil - Rivas Aratoma, Brenda; Pérez Porras, Wendy Elizabeth; Ortiz Dongo, Luis Felipe; Arévalo Aranda, Yuri Gandhi; Solórzano Acosta, Richard Andi (MDPI, 2025)
Organic amendments provide a sustainable strategy to enhance soil quality in degraded environments while also helping to reduce greenhouse gas emissions, for example, by improving soil structure, minimizing the use of synthetic fertilizers, and promoting a green economy. This study assessed the comparative effects of two organic amendments— vermicompost leachate and biochar—on the performance of popcorn maize (Zea mays L. var. everta) cultivated in saline soil conditions. Four treatments were evaluated: T0 (Control), T1 (Vermicompost leachate), T2 (Biochar), and T3 (Vermicompost leachate + Biochar), each with 10 replicates arranged in a Completely Randomized Design (CRD). Although various soil physicochemical, microbiological, and agronomic parameters displayed no significant differences compared to the control, the application of biochar resulted in considerable improvements in soil total organic carbon, the microbial community (mesophilic aerobic bacteria, molds, and yeasts), and increased seed length and diameter. In contrast, vermicompost leachate alone negatively impacted plant growth, leading to decreases in leaf area, stem thickness, and grain yield. Specifically, grain yield declined by 46% with leachate alone and by 31% when combined with biochar, compared to the control. These findings emphasize the superior effectiveness of biochar over vermicompost leachate as a soil amendment under saline conditions and highlight the potential risks of widely applying compost teas in stressed soils. It is recommended to conduct site-specific assessments and screenings for phytotoxins and phytopathogens prior to use. Additionally, the combined application of leachate and biochar may not be advisable given the tested soil characteristics.